Activated and unactivated forms of human erythrocyte aldose reductase. - Srivastava, S K (1985)
Aldose reductase (alditol:NADP+ 1-oxidoreductase, EC 1.1.1.21) has been partially purified from human erythrocytes by DEAE-cellulose (DE-52) column chromatography. This enzyme is activated severalfold upon incubation with 10 microM each glucose 6-phosphate, NADPH, and glucose. The activation of the enzyme was confirmed by following the oxidation of NADPH as well as the formation of sorbitol with glucose as substrate. The activated form of aldose reductase exhibited monophasic kinetics with both glyceraldehyde and glucose (Km of glucose = 0.68 mM and Km of glyceraldehyde = 0.096 mM), whereas the native (unactivated) enzyme exhibited biphasic kinetics (Km of glucose = 9.0 and 0.9 mM and Km of glyceraldehyde = 1.1 and 0.14 mM). The unactivated enzyme was strongly inhibited by aldose reductase inhibitors such as sorbinil, alrestatin, and quercetrin, and by phosphorylated intermediates such as ADP, glycerate 3-phosphate, glycerate 1,3-bisphosphate, and glycerate 2,3-trisphosphate. The activated form of the enzyme was less susceptible to inhibition by aldose reductase inhibitors and phosphorylated intermediates.